Proyecto de implementación y evaluación económica de una terminal de buses intercantonales en la ESPOL - González Narváez, Ronald (2009)
As widely known, the problem of ESPOL´s transporting system is the lack of commodities, accessibilities and alternatives needed in order for people to move between the campus and the final destination, may it be because of disorganization or for the lack of physical facilities in which people have the commodity to require the service. The present bus stops do not offer this, people have to stand and protect themselves from the weather and other incommodities, like the sun, rain and the huge amount of people waiting for a bus. This generates a pretty low level of satisfaction in the service users. At the present time, ESPOL has 10200 students which will serve as a reference to determine the unsatisfied order of buses, analyzed by the use of surveys, determining the number of students that live outside the city and the schedule needed for certain routes. The terminal would try to fill the gap in service that the actual service of transport of ESPOL where the community will have a strategically positioned point, where people can arrive without the necessity of looking in each faculty for a bus to take them home; this is why this project originates order and time saving for users.